Relevansi Konsep Pendidikan Akhlak Ibn Miskawaiha dengan (Wacana) Pendidikan Karakter Modern - Khasbullah, Muhammad Nabil (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2013)
This article aims at relating Ibn Miskawaih concept of character building to modern concept of character building. In Islamic history, Ibn Miskawai>h has succeeded in formulating the concept of moral guidance. His concept is a blend of historical and practical study. Ibn Miskawai>h and modern scientists have at least two things in common. Therefore, Ibn Miskawaiha moral education concept is relevant to the modern character education. That is, enriching today character education by Ibn Miskawaia moral education is worth doing.